Seed production and quality of maize in High Valleys of Mexico. - Virgen-Vargas, Juan (2015)
The objective of this study was to increase the productivity of maize in High Valleys of Mexico, at the Valley of México and Bajio Experimental Stations of the National Institute for Forestry, Agriculture and Livestock Research (INIFAP). The following activities were carried out: production of registered seed to strengthen seed micro- enterprises of national capital, quality evaluation of certified seed, and generation of production technology. Between 2005 and 2013, 46.71 tons of registered seed of the hybrids parents: H-40, H-48, H-50, H-52, H-66, H-70 and H-161, and the varieties: VS-22, V-54A and V-55A were produced and sold to 31 seed producers in the Estado de Mexico, Tlaxcala, Puebla, Hidalgo, Morelos, Guanajuato, Michoacan, and Jalisco; that satisfied 60 % of demand per year (8.68 t). In 2013 and 2014, agreements were signed between INIFAP and four micro-enterprises to produce registered seeds. The certified seed produced by companies reached certification standards, germination percentage ≥ 85, 98% pure seed and less than 2% inert matter; test weight between 72 and 78 kg/hl, thousand seed weight between 288 and 361 g and genetic quality between 96 and 98 % of the true type plants. The study identified information about locations, potential yields, population density, and planting dates for the production of parents, lines and single crosses, in the Estado de Mexico and Tlaxcala.